Particle Creation and Annihilation: Two Bohmian Approaches - Oldofredi, Andrea (Lato Sensu: Revue de la Société de philosophie des sciences, 2018)
This paper reviews and discusses two extensions of Bohmian Mechanics to the phenomena of particle creation and annihilation typically observed in Quantum Field Theory (QFT): the so-called Bell-type Quantum Field Theory and the Dirac Sea representation. These theories have a secure metaphysical basis as they postulate a particle ontology while satisfying the requirements imposed by the Primitive Ontology approach to quantum physics. Furthermore, their methodological perspective intentionally provides a set of rules to immunize physical theories to the conceptual and technical problems plaguing the standard formulation of Quantum Mechanics and QFT. A metaphysical analysis of both theories will be given, emphasizing the relevant features of each proposal. Finally, it will be acknowledged that, despite the metaphysical virtues and niceties of these frameworks, ultimately they do not provide definitive answers to other cogent foundational issues in QFT. Thus, these theories (as well as the other Bohmian extensions to QFT) should be considered as partial solutions to the problems raised by the quantum theory of fields. This situation can be considered incentive for further research.